2010
DOI: 10.2527/jas.2009-2792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadotropin treatment on estrus, ovulation, and litter size in weaned and anestrous sows1

Abstract: In the first of 2 experiments, we evaluated the effects on anestrous sows of pretreatment with FSH to stimulate the growth of small follicles, followed by eCG to stimulate the growth of medium follicles, estrus, and ovulation. In Exp. 2, we examined the effect of sows receiving 400 IU of eCG plus 200 IU of hCG (PG 600, Intervet/Schering Plough Animal Health, Boxmeer, the Netherlands) at weaning and then different doses and timing of supplemental hCG. In Exp. 1, a total of 87 multiparous Hypor sows deemed anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
2
5
0
1
Order By: Relevance
“…This would be consistent with the results of Manjarin et al [34] and Patterson et al [5]. More piglets were born to gilts and primiparous sows treated with PMSG than to untreated animals or animals injected with peforelin.…”
Section: Paritysupporting
confidence: 93%
“…This would be consistent with the results of Manjarin et al [34] and Patterson et al [5]. More piglets were born to gilts and primiparous sows treated with PMSG than to untreated animals or animals injected with peforelin.…”
Section: Paritysupporting
confidence: 93%
“…Treatment with eCG in gilts and younger sows could thus have more influence on the outcome of total born piglets, compared to the litter size in older sows. The lack of significant differences with respect to litter size among the control and treatment groups in sows is consistent with the results of earlier studies [22, 23]. do Lago et al (2005) and Martinat-Botté et al (2010) found that eCG treatment increased the ovulation rate [2, 24], leading to larger litter sizes.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of treatment with supplemental LH-like activity products (such as eCG) was shown to be age dependent [22]. Therefore it is possible that the endogenous LH support of older sows is adequate enough to support follicular development, whereas that of gilts is maybe insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in FEI throughout the different study periods could be observed, although numerical trends showed an improvement in all study periods. This indicates that GnRH-agonists have little influence on the outcome of pregnancy [19, 23] and mainly improve estrus performance. An increase of almost 9 % in FEI may have a significant biological impact on sow farm management, especially under conditions of batch management systems, where return-to-estrus and non-pregnancy can have a major impact on the batch stability.…”
Section: Resultsmentioning
confidence: 99%